In search of the lost song: between Dante and Mickey Mouse (Itinera, 2023)
This paper is intended to illustrate the possibilities offered by comics in linguistic and literary education. In particular, the subject of analysis concerns a publication by Disney, Zio Paperone e il centounesimo canto, made as a tribute to Dante and the Divina Commedia. The proposal is introduced by a reference to the mystery that surrounds various discoveries of songs of the Divina Commedia supposedly lost; it continues with a description of the comic as a medium in linguistic and literary education; the idea of language varieties and the coexistence of different languages is then presented, linking the proposal to the requirements contained in ministerial school documents. To conclude, an analysis of the language present in the balloons of the comic is carried out, with an examination of the choices made by the authors, also through references in diachrony.